Estimation of particle number and equivalent black carbon mass emission factors in Manila using the Operational Street Pollution Model - MADUENO, LEIZEL I. (Archīum Ateneo, 2017)
Urban air pollution due to vehicular emissions is associated with adverse health effects and degradation of urban air quality. Metro Manila, the capital of the Philippines, has been labeled as one of the most densely populated cities in the world. A measurement campaign, Manila Aerosol Characterization Experiment (MACE 2015), was held to assess Manila's air pollution problem. This study investigated the emission of vehicles at street level in terms of emission factors (EF) of particle number (PN) and equivalent black carbon (eBC) mass. The widely used Operational Street Pollution Model (OSPM) is applied to assess the pollutants in a street canyon in Manila. The results suggested that the Jeepney, a diesel-fed vehicle, is responsible for the majority of vehicular emissions. This study can be used as a basis for emission inventories for air quality modeling of similar vehicle types not only in Manila but also in other cities in Southeast Asia.